DEVELOPING A MULTI-OBJECTIVE SUSTAINABLE SUPPLY CHAIN NETWORK LOCATION-ALLOCATION MODEL FOR PERISHABLE PRODUCTS - Munshi, Shadi; Aziz Al-Anazi, Abdul; Al-Ashhab, M. S. (International Journal of Research -GRANTHAALAYAH, 2022)
In this paper, the problem of considering how to design and plan the Sustainable Supply Chain Network (SSCN) for perishable goods considering multi-objectives has been addressed. The proposed model targeted considerable assistance from organizations for the efficient design of SCM networks. The model aims to maximize both profit and overall customer service level while minimizing the total cost. The proposed model is formulated using MINLP and solved by GAMS/DICOPT solver. The effects of the maximum permissible deviation on the different objectives and supply chain performance are studied. The maximum allowable deviations range from 0 to 0.5 with a step of 0.1. In addition, the effect of changing the optimization order on the performance of the network performance is studied.